2018
DOI: 10.3847/2041-8213/aac6d7
|View full text |Cite
|
Sign up to set email alerts
|

A Kinematical Detection of Two Embedded Jupiter-mass Planets in HD 163296

Abstract: We present the first kinematical detection of embedded protoplanets within a protoplanetary disk. Using archival ALMA observations of HD 163296, we demonstrate a new technique to measure the rotation curves of CO isotopologue emission to sub-percent precision relative to the Keplerian rotation. These rotation curves betray substantial deviations caused by local perturbations in the radial pressure gradient, likely driven by gaps carved in the gas surface density by Jupiter-mass planets. Comparison with hydrody… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
374
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 316 publications
(400 citation statements)
references
References 41 publications
21
374
5
Order By: Relevance
“…Nevertheless, it would be interesting to include more planets and model the 10-200 au range of this system, assuming that each gap in dust continuum stems from a single planet opening a corresponding gap in gas density. This is further motivated by the kinematic detection of Jupiter-sized planets at 83 and 137 au by Teague et al (2018). We therefore carried out a simulation with three planets at 48, 86, and 145 au, respectively, and find similar results in the 10-50 au range.…”
Section: Discussionmentioning
confidence: 83%
“…Nevertheless, it would be interesting to include more planets and model the 10-200 au range of this system, assuming that each gap in dust continuum stems from a single planet opening a corresponding gap in gas density. This is further motivated by the kinematic detection of Jupiter-sized planets at 83 and 137 au by Teague et al (2018). We therefore carried out a simulation with three planets at 48, 86, and 145 au, respectively, and find similar results in the 10-50 au range.…”
Section: Discussionmentioning
confidence: 83%
“…Observations in the dust continuum using ALMA (Isella et al 2016) confirmed the existence of three gaps at distances of ∼ 50, ∼ 81 and ∼ 136 AU (corrected with the new Gaia distance of 101.5 pc). Kinematical analysis of gas observations suggested the presence of two planets at the second and third gaps (Teague et al 2018). In Pinte et al (2018), HD models showed that a third planet is expected further out.…”
Section: Hd 163296mentioning
confidence: 97%
“…The DSHARP large program (Andrews et al 2018) has confirmed that substructure is ubiquitous in large discs when observed with enough resolution, although these disc features do not necessarily confirm the presence of planets. The first indirect detection of planets at these wavelengths was achieved from detailed analyses of the gas kinematics in the HD 163296 disc (Teague et al 2018;Pinte et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The disturbed velocity pattern is detectable with high spectral and high spatial resolution ALMA line observations. Accurate measurements of rotation curves revealed for instance radial pressure gradients, likely driven by gaps carved in the gas surface density by Jupiter-mass planets in the disk of HD 163296 (Teague et al 2018a). In a given channel map, the emission is concentrated along the iso-velocity curve, i.e., the region of the disk where the projected velocity is constant.…”
Section: Introductionmentioning
confidence: 99%